2015
DOI: 10.5301/ejo.5000570
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neutrophil/Lymphocyte Ratio and Retinal Vein Occlusion

Abstract: The current study demonstrated that higher NLR was associated with the development of RVO. The NLR may be used as a predictive tool for identifying risk for RVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
37
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 38 publications
6
37
2
1
Order By: Relevance
“…Dursun et al compared 40 patients with retinal vein occlusion with a control group and found that the NLR levels of patients with retinal vein occlusion were significantly higher than those in control patients. [19] The sensitivity and specificity of NLR reported by Dursun et al were found to be 72% and 100%, respectively (cut-off value: 1.89), whereas in our study, these figures were 72% and 69%, respectively (cut-off value: 1.82). [19] PLR, which is calculated via dividing a patient's platelet count by the number of lymphocytes, is a cheap and easy test that reveals the condition of platelets and white blood cells.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Dursun et al compared 40 patients with retinal vein occlusion with a control group and found that the NLR levels of patients with retinal vein occlusion were significantly higher than those in control patients. [19] The sensitivity and specificity of NLR reported by Dursun et al were found to be 72% and 100%, respectively (cut-off value: 1.89), whereas in our study, these figures were 72% and 69%, respectively (cut-off value: 1.82). [19] PLR, which is calculated via dividing a patient's platelet count by the number of lymphocytes, is a cheap and easy test that reveals the condition of platelets and white blood cells.…”
Section: Discussioncontrasting
confidence: 85%
“…[19] The sensitivity and specificity of NLR reported by Dursun et al were found to be 72% and 100%, respectively (cut-off value: 1.89), whereas in our study, these figures were 72% and 69%, respectively (cut-off value: 1.82). [19] PLR, which is calculated via dividing a patient's platelet count by the number of lymphocytes, is a cheap and easy test that reveals the condition of platelets and white blood cells. Thrombocytes play a significant role in coronary artery disease and cardiovascular disorders.…”
Section: Discussioncontrasting
confidence: 85%
“…[11] Oküler hastalıklar sistemik inflamasyondan ziyade lokal bir inflamatuar yanıta neden olmasına rağmen NLO'nun yaşa bağlı makular dejenerasyon, retinal ven tıkanıklığı, non-arteritik anterior iskemik optik nöropati, vernal keratokonjonktivit, kuru göz ve primer açık açılı glokom gibi çeşitli göz hastalıklarında ilişkili olduğu saptanmış-tır. [25][26][27][28][29][30][31] NLO'nun lokal inflamatuar hastalıklarda anlamlı olabilmesi için sistemik kan parametrelerinde değişiklik yapması gerekir. TO'deki inflamasyon aslında sistemik inflamasyonun bir sonucudur ve kan parametrelerini değiştirebilir.…”
Section: Discussionunclassified
“…Ilhan et al (21) reported that an elevated NLR can be a potential indicator of vitreomacular traction syndrome, regardless of the etiology. Dursun et al (22) suggested that the optimal cut-off value of NLR to predict retinal vein occlusion with 72.5% sensitivity and 100% specificity was 1.89. These reports revealed the critical role of inflammatory cascades in the pathophysiology of these diseases and the diagnostic value of NLR.…”
Section: Discussionmentioning
confidence: 99%